2022
DOI: 10.3390/app122312095
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Trough Study of the Interactions of Tear Mimetic Eyedrop Formulation with Human Meibum Films

Abstract: Meibomian gland disease is associated with quantitative or qualitative deficiencies of meibum (MGS) that result in tear film instability. Thus, there is great demand for ophthalmic nanoemulsions that can replenish MGS and recover its performance at the air/tear surface. Rohto Dry Aid (RDA) utilizes TEARSHIELD TECHNOLOGYTM implementing a complex oil phase of non-polar and polar lipid-like molecules. Therefore, the interactions of RDA with MGS surface films deserve further study as they may provide valuable insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…As shown in a previous study [12], similarly to other oil-in-water ophthalmic nanoemulsions with comparable compositions, RDA films exhibited typical behavior [24,25]. Highly reversible, non-collapsible surface films are formed by nanoemulsion.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…As shown in a previous study [12], similarly to other oil-in-water ophthalmic nanoemulsions with comparable compositions, RDA films exhibited typical behavior [24,25]. Highly reversible, non-collapsible surface films are formed by nanoemulsion.…”
Section: Discussionsupporting
confidence: 74%
“…As the continuous structure of the TFLL is an important indication for its ability to stabilize the tear film in vivo, this is an interesting result that hints at the clinical promise of opththalmic nanoemulsion applications to treat lipid-deficiency-related forms of dry eye. BAM visualization (Figure 4) revealed that while nMGS formed continuous films of multilayer thickness (estimated at around 60-100 nm, as explained previously) [9][10][11][12], in contrast dMGS layers were patchy and consisted of darker regions, probably of monolayer thickness, and thick bright regions which cannot enclose to a continuous structure and instead form a sparse bright mesh at the aqueous interface. For such estimations a simple semi-quantitative model relates the intensity, I, of the film regions in the BAM image with its thickness, d (d i /d j = [I i /I j ] 1/2 , where the subscripts i and j denote the different images) [3].…”
Section: Effect Of Rohto Dry Aid On Dmgs Filmssupporting
confidence: 70%
See 3 more Smart Citations